CRITICAL DISCOURSE ANALYSIS ON CHINESE AND AMERICAN NEWS WEBSITES REPORTING SOUTH CHINA SEA TERRITORIAL DISPUTE - Fawwaz Aldi Pradana; Suprayogi Suprayogi (Linguistics and Literature Students' Journal, 2021)
This study focuses to understand the differences in reporting the same of The South China Seaterritorial dispute by two international news websites namely The New York Times and China Dailyand to exposed the hidden ideology behind the representation of those news websites. ThreeDimensional Framework by Fairclough in Critical Discourse Analysis were used in this study alongwith Systemic Functional Grammar particularly in transitivity analysis. The articles in this study werecollected from China Daily and The New York Times news website. The finding revealed that bothnews websites reported the issue of territorial dispute using material process and verbal processdominantly but The New York Times dominantly use material process more than China Daily. Next,the study found out that China Daily depicted the act of Beijing saying that territorial dispute as anormal thing due to the area of water are belong to China while The New York Times depicted the actof China as a violation of Sea rules of navigation in responding the territorial dispute. Last, the resultof this study found that China Daily stated in its news about how the US presence as meddling in thedisputed area of The South China Sea while The New York Times stated that the act of China inresponding the dispute is a harsh attitude and violating the rules. To sum up the study, thecombination of both theories is somehow useful in the discourse to expose the hidden meaning andideology.Keywords: Constrastive study, territorial dispute, three dimensional framework